INVESTIGATION ON CHEMICAL COMPOSITION, ANTIMICROBIAL, ANTIOXIDANT, AND CYTOTOXIC PROPERTIES OF ESSENTIAL OIL FROM DRACOCEPHALUM KOTSCHYI BOISS - Ashrafi, Behnam; Ramak, Parvin; Ezatpour, Behrouz; Talei, Gholam Reza (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Dracocephalum kotschyi Boiss is a herb with wide-spread applications. Lorestan traditional healers haveapplied it for the treatment of rheumatoid diseases and stomach disorders.Materials and methods: Hydrodistillation process was used for essential oil extraction, the extracted essential oil wasthen analyzed through combination of capillary GC–FID, GC–MS and RI. The in vitro antimicrobial, antioxidant andcytotoxic activities of this essential oil were examined. Results indicate that the essential oil has a broad range of antimicrobialactivity against all of the tested microorganisms.Results: The 50% of cytotoxic concentrations was 26.4 μg/ml and 4266.7 μg/ml for Hela cells and humanlymphocytes, respectively. The oil cytotoxicity against the human tumor cell line was far higher than the amountrequired for human healthy cells. Conversely, the essential oil’s IC50 value of 49.2 μg/ml in the DPPH assay, could beregarded as its strong antioxidant potential.Conclusion: According to the data obtained, it can be concluded that D. kotschyi essential oil could be applied as a safeantibacterial and antioxidant agent for food and pharmaceutical purposes.